Coaggregation of Candida albicans, Actinomyces naeslundii and Streptococcus mutans is Candida albicans strain dependent - Arzmi, Mohd Hafiz; Stuart, Dashper; Nicola, Cirillo; Eric, Reynolds; Michael, McCullough (Wiley-Blackwell, 2015)
Microbial interactions are necessarily associated with the development of polymicrobial oral bio lms. The objective of this study was to determine the coaggregation of eight strains of Candida albicans with Actinomyces naeslundii and Streptococcus mutans. In autoaggregation assays, C. albicans strains were grown in RPMI-1640 and arti cial saliva medium (ASM) whereas bacteria were grown in heart infusion broth. C. albicans, A. naeslundii and S. mutans were suspended to give 106, 107 and 108 cells mL−1 respectively, in coaggregation buffer followed by a 1 h incubation. The absorbance difference at 620 nm ( Abs) between 0 h and 1 h was recorded. To study coaggregation, the same protocol was used, except combinations of microorganisms were incubated together. The mean Abs% of autoaggregation of the majority of RPMI-1640-grown C. albicans was higher than in ASM grown. Coaggregation of C. albicans with A. naeslundii and/or S. mutans was variable among C. albicans strains. Scanning electron microscopy images showed that A. naeslundii and S. mutans coaggregated with C. albicans in dual- and triculture. In conclusion, the coaggregation of C. albicans, A. naeslundii and S. mutans is C. albicans strain dependent.